Exploring Metacognitive Strategies In English Language Learning For Non-Language Students - Imran, Fathurrahman; Tawali, Tawali; Jumadil, Jumadil (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to describe the application of metacognitive strategies in English language learning among students of the Management Study Program at Mandalika University of Education. Metacognitive strategies are considered important because they help students manage their thinking processes, organize learning strategies, and reflect on learning outcomes. This study uses a mixed methods approach with quantitative and qualitative descriptive approaches. A total of 35 active students were selected as respondents through purposive sampling. Data were collected using a metacognitive strategy questionnaire and semi-structured interviews. Descriptive analysis results show that the overall level of metacognitive strategy application among students is in the high category with an average score of 3.98. The planning dimension ranked highest with an average score of 4.18, followed by the monitoring dimension with a score of 3.92, and the evaluating dimension with a score of 3.85. Qualitative findings supported these results by showing that most students had good learning awareness, although the aspects of reflection and self-evaluation were not carried out consistently. The results of this study confirm that the application of metacognitive strategies plays an important role in shaping independent and reflective learners, as well as forming the basis for the development of a more effective English learning model for non-language students in higher education.